The Effect of Zinc Dialkyl Dithiophosphate (ZDDP) Additive on the Tribological Properties of Mahogany (Khaya senegalensis) Seed Oil - Ayuba, D.M.; Hammajam, A. A.; Abba-Aji, M. A.; Amos, C. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2025)
Mineral oil based lubricants are non-renewable, harmful to health and prone to price fluctuations. Thus, vegetable oils are considered as suitable alternatives to mineral oils for lubricant production. As such, new research into the use of non-edible vegetable oils for lubricant development is advocated to address these challenges. In this study, tribological evaluation of lubricant developed from non-edible vegetable mahogany (Khaya senegalensis) oil for industrial applications was conducted. Interestingly, the oil was characterized, modified for suitability and used to develop lubricants for industrial applications. Additionally, commercially available mineral oil based lubricant SAE 20/W50 was used as a control. The effect of ZDDP additive on the tribological performance of mahogany seed oil based biolubricant developed was also studied. The results show that the developed mahogany seed oil based biolubricant had alkaline pH of 7.56, high viscosity index of 147.12, appreciable viscosity, excellent cold flow of -9.2 ºC. Similarly, the coefficient of friction of the biolubricant developed reduced from 0.095 to 0.090when 1% of ZDDP was added and form 0.095 to 0.087 when 3% of ZDDP was added but the coefficient of friction increased from 0.095 to 0.099 with the addition of 5% of ZDDP. Therefore, developed mahogany seed oil biolubricant was observed to be suitable and environmentally friendly substitutes to mineral oil base lubricant SAE 20/W50 for application in metal cutting and lubrication of gears in food processing industry.